Plasma Microbial Cell-Free DNA Sequencing Technology for the Diagnosis of Sepsis in the ICU - Wang, Lili; Guo, Wenzheng; Shen, Hui; Guo, Jian; Wen, Donghua; Yu, Yuetian; Wu, Wenjuan (Frontiers in Molecular Biosciences, 2021)
Sepsis is a common life-threatening disease in the intensive care unit (ICU) that is usually treated empirically without pathogen identification. As a non-invasive and high-throughput technology, plasma microbial cell-free DNA (mcfDNA) sequencing can detect unknown pathogens independent of previous clinical or laboratory information. In this study, a total of 199 cases suspected of bloodstream infection (BSI) from January 2020 to June 2020 were collected, and potential pathogens were detected by simultaneous blood culture and plasma mcfDNA sequencing. Other clinical microbiological assays were performed within 7 days of plasma mcfDNA sequencing, including smear, culture of samples taken from relevant infected sites, and β-D-glucan/galactomannan (BDG/GM) tests, among others. The diagnoses were classified as sepsis (94 [47.2%]), non-sepsis (87 [43.7%]), and non-infectious disease (18 [9.0%]). The sensitivity and specificity of plasma mcfDNA sequencing for diagnosing sepsis were 68.1% and 63.2%, respectively, which were significantly better than those of blood culture, especially for the common bacteria that cause hospital-acquired infection, namely, Acinetobacter baumannii (p < 0.01) and Klebsiella pneumoniae (p < 0.01), and DNA viruses (plasma mcfDNA sequencing only, p < 0.01). However, there was no significant difference in the rate of positivity between plasma mcfDNA sequencing and blood culture for antibiotic-non-exposed cases (43.6 vs 30.9%, p = 0.17). In the non-sepsis group, 44.8% of cases (13/29) detected only by plasma mcfDNA sequencing showed infections in other parts of the body, such as lower respiratory infection (LRI), intra-abdominal infection (IAI) and central nervous system infection (CNSI). For some common pathogens (not including anaerobes), turnaround time (TAT) 3 (TAT from the initiation of blood sample processing by nucleic acid extraction to the completion of sequencing analysis) was longer than TAT1 (TAT from blood culture bottles in Virtuo to off Virtuo). With disease progression, significant dynamic changes in microbial species were clearly detected by plasma mcfDNA sequencing.